Microwave and Ultrasound Irradiations for the Intensification on Biodiesel Productions: a Mini Review - Suresh Sagadevan; Amri Yahya; Is Fatimah (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
This mini review discusses the roles of intensification process in biodiesel production. Due to the Twelve Principles of Green Chemistry as a foundation for sustainability, the shorter time and efficient energy consumption highlighted the use of microwave and ultrasound irradiation for increasing conversion of biodiesel.The principles and some examples for the process are exhibited. It can be summarized that the intensifications are important innovations, but some optimization and life cycle analysis are required in applicable scales.